Massive Upper Body and Cervicofacial Subcutaneous Emphysema Following Robotic Myomectomy - Joseph Capone; Aladino De Ranieri; Nebojsa N. Knezevic; Ivan K. Lukić; Kenneth Candido; Vicko Gluncic (Case Reports in Anesthesiology)
Subcutaneous emphysema is defined as the unintentional introduction of air or carbon dioxide in the subcutaneous tissues. The use of robotic surgical techniques has greatly expanded over the past decade specifically to treat intraperitoneal pathology. In general, advantages of these minimally invasive procedures are reported to decrease operating time, patient morbidity, and shorten hospital stay providing a safe alternative to traditional surgery. However, as with any surgery, potential complications may occur. We describe an unusual case of massive subcutaneous emphysema involving the upper body and cervicofacial region, with bilateral pneumothoraces following robotic intraperitoneal surgery. Written authorization was obtained from the patient.